Development of a high resolution MRI intracranial atherosclerosis imaging phantom. (9th March 2017) - Chueh, Ju-Yu; van der Marel, Kajo; Gounis, Matthew J; LeMatty, Todd; Brown, Truman R; Ansari, Sameer A; Carroll, Timothy J; Buck, Amanda K; Zhou, Xiaohong Joe; Chatterjee, A Rano; King, Robert M; Mao, Hui; et al.
Abstract : Background and purpose: Currently, there is neither a standard protocol for vessel wall MR imaging of intracranial atherosclerotic disease (ICAD) nor a gold standard phantom to compare MR sequences. In this study, a plaque phantom is developed and characterized that provides a platform for establishing a uniform imaging approach for ICAD. Materials and methods: A patient specific injection mold was 3D printed to construct a geometrically accurate ICAD phantom. Polyvinyl alcohol hydrogel was infused into the core shell mold to form the stenotic artery. The ICAD phantom incorporated materials mimicking a stenotic vessel and plaque components, including fibrous cap and lipid core. Two phantoms were scanned using high resolution cone beam CT and compared with four different 3 T MRI systems across eight different sites over a period of 18 months. Inter-phantom variability was assessed by lumen dimensions and contrast to noise ratio (CNR). Results: Quantitative evaluation of the minimum lumen radius in the stenosis showed that the radius was on average 0.80 mm (95% CI 0.77 to 0.82 mm) in model 1 and 0.77 mm (95% CI 0.74 to 0.81 mm) in model 2. The highest CNRs were observed for comparisons between lipid and vessel wall. To evaluate manufacturing reproducibility, the CNR variability between the two models had an average absolute difference of 4.31 (95% CI 3.82 to 5.78). Variation in CNR between the images from the same scanner separated by 7 months was 2.5–6.2, showing reproducible phantom durability. Conclusions: A plaque phantom composed of a stenotic vessel wall and plaque components was successfully constructed for multicenter high resolution MRI standardization.